Rheological characterization of the exopolysaccharide Paenan in surfactant systems. (1st February 2018) - Rütering, Marius; Schmid, Jochen; Gansbiller, Moritz; Braun, Andre; Kleinen, Jochen; Schilling, Martin; Sieber, Volker
Highlights: Thorough rheological characterization of Paenibacillus sp. derived Paenan polysaccharide. Weak-gel character suggests novel application profile between commercial benchmarks. Rheological comparison to Xanthan and Gellan in surfactant-containing systems. Unique surfactant-compatibility renders Paenan interesting for several applications. Abstract: Rheology-controlling agents are of importance for numerous products in a variety of industries. Replacement of synthetic chemicals with natural additives is desired in light of current environmental awareness and limited fossil resources. This study investigates the rheological features of Paenan, an exopolysaccharide produced by Paenibacillus polymyxa . Paenan exhibits highly shear-thinning flow behavior at concentrations ≥0.1% in 0.5% NaCl. Because of its pronounced intermolecular network, it forms stable, weak gels, thereby delivering elasticity as well as thixotropy. Application-relevant flow behavior is obtained with 60–65% less polymer as compared to the benchmark commercial products Xanthan and Gellan. In mixtures with surfactants (sodium lauryl ether sulfate, cetrimonium chloride, cocamidopropyl betaine, or lauryl glucoside), Paenan displays outstanding compatibility with every class of surfactant, making it superior to the partially incompatible Xanthan and Gellan. The weak-gel character of Paenan/surfactant systems is retained with three out of four surfactants, rendering Paenan highly interesting for various applications.